Jesus as wandering prophetic wisdom teacher - Donneyer, D. (Hervormde teologiese studies, 1993)
The view on Jesus as a wandering wisdom teacher reveiles that “wandering’ was one of the basic concepts of theology. It is interesting to take note that the title ‘teacher’ was given to Jesus, not by his own discples, but by ‘outsiders’, because of his public activities. Three qualities are attached to Jesus as wisdom teacher: prophecy, miracle working and wandering. In this paper the Gospel of Mark is explored to dipict the road Jesus walked from Galilee to Jerusalem - always without a planned itinarary. The conclusion is that ‘wandering’ is a central action of Jesus throughout the New Testament, in a physical as well as a metaphorical-theological way.